ANALISIS FATWA MUI HALALNYA KEPITING - Muslihan Habib (Sekolah Tinggi Agama Islam AL Aqidah Al Hasyimiyyah Jakarta, 2018)
The position of mufti (giver of fatwas) is crucial to mustafti (peminta fatwa). The mufti has to have the skills of Shari'ah and able to read the situation and condition well. The mufti as the tongue of the Prophets. The facts show of mufti with its fatwas widely used countries, such as banking, halal food and beverages, drugs and so on, determine government policy specially Ministry of Religious Affairs of the Republic of Indonesia. Crabs according to Fatwa MUI may be eaten. Crabs are not animals that live in two realms, land and water. Crabs are marine animals or rivers, so the medium of life is water. Crabs that are on land, can survive because of the water pockets in the shell.